If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(q + 1) = 20 Reorder the terms: 2(1 + q) = 20 (1 * 2 + q * 2) = 20 (2 + 2q) = 20 Solving 2 + 2q = 20 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2q = 20 + -2 Combine like terms: 2 + -2 = 0 0 + 2q = 20 + -2 2q = 20 + -2 Combine like terms: 20 + -2 = 18 2q = 18 Divide each side by '2'. q = 9 Simplifying q = 9
| 1.50x+4y=722 | | a^4-3a^2-4=0 | | x^3=1.33 | | 20-x-3(2x+1)=12 | | 6x^3y-24xy^4/8y^3-2x^2=0 | | 7.4=-3.4+s | | 4x+3x+25=7x+25 | | 9x-33=-38 | | 6x+2=-12x+9+5x | | 6x+2=-12+9+5x | | 3600=120x-x^2 | | 10y-2=6y+12 | | square(7-x)=0 | | 3x+6=r+10 | | 2x-5(x+4)=-7+4x-8 | | 2Y+8+X=180 | | X+5=2x+24 | | 11-6x=1-x | | 19-13b=6b+78 | | 13x-9=5x+11 | | y/-5=6m | | 2m-12=7m-41 | | a+3a-15=25-2a+6 | | 4/5c-36=8 | | 50-1/3x=70-x | | 3x-5+2x=12-x | | 3x^2-10=-46 | | -29-7x=-5(6x-8) | | 7-12x=3x+32 | | -5q=-30 | | (-4mn^2)(2m^4n^2)= | | 4p+9=1 |